Youth Labor Migration in Nepal - Bossavie, Laurent; Denisova, Anastasiya (World Bank, Washington, DC, 2018)
This descriptive study investigates internal and external labor migration by Nepalese youth. External labor migration is separated into the flow to India, which is unregulated, and the flow to other countries, which typically takes the form of temporary contract migration to countries with bilateral labor agreements with Nepal (referred to in Nepal as foreign employment). The study finds that labor migration by Nepalese youth is extensive and male dominated. The regions with the highest rates of labor outmigration are rural Terai, rural Hills, and Mountains. Female labor migration is mostly within Nepal, whereas male labor migration is mostly to other countries. Most labor migrants are wageemployed, and engage in services. Labor migration is positively associated with education attainment for women, but negatively associated for men. Labor migration is also positively associated with household economic status for women. Just four destination countries (Malaysia, Qatar, Saudi Arabia, and the United Arab Emirates) account for the majority of foreign employment workers. Nepal’s foreign employment system faces several challenges, including implementation shortcomings in the government’s institutional arrangements for workers, and the substantial market power of private recruitment agencies over workers. Male foreign employment outflow appears to be mainly associated with economic and other forces in the top destination countries. Male youth labor migration has negative effects on the likelihood of employment and hours worked for female and male youth household members who remain at home, although the effects are not consistently significant.